Spontaneous pneumomediastinum: a benign pathology? analysis of 25 cases and review of the literature - Baeza Carrión, Ana; Cornejo López, María de los Ángeles; Garrido Benito, Beatriz; Pascual Nadal, Juan José; Velayos García, Paula; Ripoll Martín, Roberto; Ots Gutiérrez, José Ramón; Oliver García, Israel (Cirugía del Uruguay, 2021)
Introduction and objectives: Spontaneous pneumomediastinum is defined as interstitial air in the mediastinum with no established primary cause that predominates in young adult males. The objective of this study is to inform about the usual management in our hospital and to propose a diagnostic-therapeutic algorithm. Materials and methods: Descriptive and retrospective study of 25 cases of spontaneous pneumomediastinum diagnosed at our hospital, in a period of 25 years. Demographic data, predisposing and triggering factors, symptoms, diagnosis, treatment, and recurrences were analyzed. Results: The mean age was 22 years, with asthma, drug inhalation, tooth extractions, or smoking as predisposing factors. The most frequent symptoms were chest pain, dyspnea, dysphonia, and dysphagia / odynophagia. The initial diagnosis was obtained by chest x-ray, sometimes being completed with computerized tomography, esophagogram, or laryngoscopy. All patients were admitted conservatively. During follow-up, 12 % presented recurrence of the pneumomediastinum, which resolved without complications. Discussion: The presence of free mediastinal air can be perceived as a finding of poor prognosis, but previous studies conclude that spontaneous pneumomediastinum has a benign course, although the diagnosis must be made by exclusion, since the bulk of the evidence is secondary pneumomediastinum. Conclusions: Spontaneous pneumomediastinum is a benign and infrequent entity that may have predisposing and triggering factors, although there is no apparent primary cause. It usually resolves conservatively in a few days, although there may be recurrences.